The Influence of Transformational Leadership, Job Satisfaction, and Burnout on Turnover Intention among Gen-Z Employees in Start-Up Companies in Indonesia - Ryan Kharisma RAKHMAT; Mentiana SIBARANI (PT Keberlanjutan Strategis Indonesia, 2025)
This study investigates the influence of transformational leadership, job satisfaction, and burnout on turnover intention among Generation Z employees in Indonesian start-up companies. Utilizing a quantitative research approach with 150 respondents from fintech, e-commerce, and logistics start-ups in Jakarta and Bandung, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that transformational leadership significantly enhances job satisfaction and reduces burnout, but it does not directly affect turnover intention. Burnout significantly increases turnover intention, while job satisfaction does not serve as a significant mediator in the relationship between transformational leadership or burnout and turnover intention. These results highlight burnout as a critical factor driving employee turnover and suggest that leadership strategies alone are insufficient to retain Gen Z talent. The study underscores the importance of addressing emotional well-being, work-life balance, and organizational support systems to mitigate turnover in high-pressure start-up environments.